2016
DOI: 10.1245/s10434-016-5228-x
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Tumor Volume Assessment in Resectable Esophageal Cancer

Abstract: Tumor volume may predict survival, margin status, and lymph node positivity after surgery for esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The ve value based on the DCE-MRI scans reflects the ratio of the volume of the contrast agent in the extravascular extracorporeal space, which is indicative of tumor proliferation. Tuillie et al have shown that when tumor grade increases, pathological tumor volume and cell density value also increase (22); meanwhile, Chen et al demonstrated that a higher ve value is associated with a higher tumor T stage (23). In the present study, the rate of tumor proliferation in the PR group was higher than that in the CR group; thus, the value of ve in the PR group was higher than that in the CR group.…”
Section: Discussionsupporting
confidence: 40%
See 1 more Smart Citation
“…The ve value based on the DCE-MRI scans reflects the ratio of the volume of the contrast agent in the extravascular extracorporeal space, which is indicative of tumor proliferation. Tuillie et al have shown that when tumor grade increases, pathological tumor volume and cell density value also increase (22); meanwhile, Chen et al demonstrated that a higher ve value is associated with a higher tumor T stage (23). In the present study, the rate of tumor proliferation in the PR group was higher than that in the CR group; thus, the value of ve in the PR group was higher than that in the CR group.…”
Section: Discussionsupporting
confidence: 40%
“…Tuillie et al. have shown that when tumor grade increases, pathological tumor volume and cell density value also increase ( 22 ); meanwhile, Chen et al. demonstrated that a higher ve value is associated with a higher tumor T stage ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…With a background incidence of oesophageal cancer in Finland at the time of 4.3 per 100 000 they were only able to exclude a prevalence of oesophageal cancer in patients born with OA of greater than 500 times that of the background population. Of note, patients in the present analysis developed oesophageal cancer at a younger age (median 40.5 years) than the general population, where the median age at diagnosis is around 64 years 79 .…”
Section: Discussionmentioning
confidence: 61%
“…GTVp was then found to be an independent prognostic factor for OS and PFS. Recently, several studies have reported a close association between survival outcome and tumor volume in EC [ 19 , 20 ], but the optimal cut-off points of GTVp varied among studies. Créhange et al [ 7 ] initially found that the optimal cut-off point for differences in OS was 100 cm3.…”
Section: Discussionmentioning
confidence: 99%